Preparation method of environment-friendly water-based polishing liquid for optical glass
By using nano-cerium oxide emulsion with high-shear in-situ anchoring of bio-based chelating agents and surfactants, combined with polymeric dispersants and organic amines to adjust the pH value, an environmentally friendly water-based polishing slurry was prepared, solving the problems of abrasive agglomeration and corrosion, and achieving efficient and environmentally friendly optical glass polishing.
Patent Information
- Application Number
- CN202610329568.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-18
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies using nano-cerium oxide polishing slurries suffer from uneven abrasive particle size distribution, easy agglomeration leading to physical scratches, and often introduce strong alkalis or fluorides, resulting in corrosiveness and high-cost waste liquid treatment issues, making it difficult to achieve efficient polishing under environmental protection conditions.
A stable molecularly modified layer is formed by using nano-cerium oxide emulsion with bio-based chelating agents and surfactants for high-shear in-situ anchoring, combined with polymeric dispersants and organic amines to adjust the pH value, and then preparing an environmentally friendly water-based polishing fluid through ultrasound and precision filtration.
It achieves monodispersity and low residue of abrasive, improves polishing rate and surface roughness, reduces operational hazards and environmental treatment costs, and is suitable for precision polishing of optical glass.
Smart Images

Figure CN122628672A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical mechanical polishing technology, specifically to a method for preparing an environmentally friendly water-based grinding and polishing slurry for optical glass. Background Technology
[0002] In recent years, with the rapid development of the optical industry and precision manufacturing technology, the application of chemical mechanical polishing (CMP) technology using cerium-based materials for precision glass and semiconductor components has become increasingly widespread. Cerium oxide, with its unique chemical mechanical synergistic polishing mechanism for silicate glass, has become a core abrasive in the field of precision polishing. However, due to the extremely high surface energy of nano-cerium oxide, it is prone to spontaneous aggregation in water-based systems, leading to uncontrolled abrasive particle size distribution. The resulting coarse particles will produce severe physical scratches during processing, making it difficult to meet the stringent requirements for atomic-level surface roughness of precision components such as K9 optical glass.
[0003] To address the aforementioned issues, existing technologies have been researched. For example, patent CN110041831A discloses a nano-cerium oxide polishing slurry, which is prepared by ultrasonically dispersing nano-cerium oxide in a water-glycerol mixture and then adding a composite surfactant. Although this technology improves the uniformity and stability of the slurry to some extent, prevents crystallization and residue, and achieves a low roughness of <0.3nm on optical glass, when polishing high-hardness optical glass, a single dispersion system often cannot provide a sufficient chemical removal rate, limiting processing efficiency.
[0004] Furthermore, patent CN116004122B discloses an alkaline cerium dioxide polishing slurry employing a mild alkaline modifier and dispersants including polyacrylates or polymethacrylates. This approach achieves stable dispersion of spherical or near-spherical CeO2 particles without the use of strong alkalis or fluorides, reducing scratches caused by irregular particles and improving removal rates. However, in actual industrial recycling, stabilizers and dispersants primarily rely on the weak interactions between the abrasive surfaces. Under the high shear forces of polishing equipment, these components are prone to desorption, leading to slurry instability, and scratch control still depends on complex precision grading processes.
[0005] Furthermore, patent CN105733445A explores controlling the particle size of nano-cerium oxide through mechanochemical ball milling, and adding stearic acid or ethylene glycol and optional fluorinating agents to reduce surface defects. While this reduces agglomeration and improves uniformity during the synthesis stage, thereby reducing polishing defects, the process primarily focuses on the pretreatment of the abrasive. The lack of dynamic repair and molecular-level protection of the active sites on the cerium oxide surface during slurry preparation leads to the formation of soft agglomerates during storage. Currently, to maintain polishing activity, some industrial solutions still introduce strong alkali regulators or fluorine-containing components, resulting in highly corrosive slurries and costly treatment of the generated acidic wastewater, which violates the principles of modern green manufacturing.
[0006] In summary, achieving deep integration of additives and abrasives through efficient processes while eliminating harmful fluorides and strong alkaline systems, and resolving the contradiction between high removal rates and ultra-low roughness, remains a key technological bottleneck in the development of CMP polishing slurries. To address this, a method for preparing an environmentally friendly water-based grinding and polishing slurry for optical glass is proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing an environmentally friendly water-based abrasive polishing slurry for optical glass. The method involves high-shear in-situ anchoring of nano-cerium oxide emulsion with a bio-based chelating agent and a surfactant to achieve chemical modification of the abrasive surface; the addition of a polymeric dispersant to improve dispersion stability; adjustment of the pH to alkaline using an organic amine; and final product obtained through ultrasonication and precision filtration. This method abandons the traditional strong alkali and fluoride system, improving polishing rate and reducing surface roughness while being environmentally friendly. The slurry exhibits excellent monodispersity, low residue, and process stability, resolving the contradiction between scratch control and high-efficiency processing, and is suitable for precision polishing of optical glass.
[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing an environmentally friendly water-based polishing slurry for optical glass. The specific preparation method is as follows: (1) Abrasive surface pretreatment and chelation induction: 720g of deionized water was added to a high-shear reactor at room temperature (22℃), and stirring was started at 800rpm. 15g of chelating agent and 5g of alkyl glycoside surfactant were added sequentially, and stirring was continued for 20min to ensure complete molecular diffusion. Subsequently, 250g of nano-cerium oxide emulsion was pumped in at 10g / min, and the temperature was raised to 45-50℃. High-shear stirring was maintained at 4000-5000rpm for 1.5h. The system temperature was maintained at 45-50℃ through cooling water circulation in the reactor jacket. The chelating agent was selected from polydentate amino acid chelating agents and nitrogen-containing organic alcohol amines.
[0009] (2) Steric hindrance stabilization of polymers: Add 10-12g of dispersant to the system, reduce the stirring speed to 1200rpm, and continue dispersing for 45min. Through the dual effects of charge repulsion and steric hindrance, the particle size distribution of the abrasive is locked, preventing soft agglomeration and scratches.
[0010] (3) System balance and precision purification: The pH of the system was stabilized to 9.8-10.5 using a regulator, and then circulated through an online ultrasonic homogenizing system at a flow rate of 60 L / h, a power of 800 W, and a frequency of 40 kHz for 30 min. Finally, it was filtered through a 0.2 μm polyethersulfone precision filter and packaged to obtain the finished product.
[0011] Preferably, the regulator used to adjust the system to alkalinity is one of aminobutanol and triethanolamine. Triethanolamine replaces aminobutanol, taking advantage of its combined lubricating and weak complexing properties.
[0012] The environmentally friendly water-based polishing slurry prepared above was used to perform precision polishing tests on K9 optical glass components: constant temperature polishing at 22℃ was conducted using a 380-type single-sided precision polishing machine. CMP polishing was performed on a polyurethane foam pad with a Shore D hardness of 55-60, using a 100-mesh diamond dressing disc. Online dressing was performed every three discs for 2 minutes to maintain the microporous activity of the polyurethane polishing pad surface and prevent physical scratches caused by abrasive buildup. The polishing pressure was 35 kPa, the polishing disc speed was 85 rpm, the polishing slurry flow rate was 120 ml / min (circulated), and the polishing time was 15 minutes.
[0013] After polishing, the product was cleaned for 5 minutes with a 0.5% alkyl glycoside dilution solution under 40kHz ultrasonic conditions, then treated with deionized water at 80kHz high frequency for 3 minutes, and finally dehydrated by slow lifting with isopropanol, with the lifting speed controlled at 1-5mm / s.
[0014] The preferred method for preparing the nano-cerium oxide emulsion is as follows: 1020g of cerium nitrate is dissolved in 1500ml of deionized water, and 5g of PEG-400 dispersant is added. Magnetic stirring at 500rpm is initiated until the solution is completely transparent. The role of PEG is to encapsulate the primary crystal nuclei and prevent the particles from becoming too large later. Under vigorous stirring at 1200rpm, 150ml of hydrogen peroxide (30% concentration) is slowly added to the cerium nitrate solution. At this point, the solution color changes from colorless to deep orange, forming a cerium peroxide complex. Subsequently, 25% ammonia solution is added dropwise at a rate of 15ml / min using a peristaltic pump, with strict monitoring of the pH value. The addition is stopped when the pH value reaches 9.0-9.5, at which point a large amount of light yellow precipitate is produced. The resulting precipitate suspension is transferred to a high-pressure reactor and kept at a constant temperature of 160℃ for 12h. The hydrothermal environment promotes the transformation of amorphous cerium hydroxide into cubic fluorite CeO2 and causes the particles to spontaneously grow into spherical shapes. The hydrothermal product was separated by centrifugation. The supernatant was discarded, and the precipitate was washed repeatedly with deionized water 3-5 times until the conductivity of the centrifuged liquid was below 50 μS / cm. This step was to remove residual NH4+. 4+ and NO 3- Ions. The washed nanoparticles were redispersed in deionized water and circulated three times using a high-pressure homogenizer at a pressure of 800 bar. The moisture content was measured by a moisture analyzer. Finally, deionized water was added to precisely adjust the solid content to 40.3%, resulting in the finished nano-cerium oxide emulsion with an average particle size (D50) of 100 nm-120 nm.
[0015] Preferably, the multidentate amino acid chelating agent is selected from one of tetrasodium glutamate diacetate and trisodium methylglycine diacetate. By utilizing tetrasodium glutamate diacetate or similar agents to perform in-situ molecular coating on the CeO2 surface at a specific temperature, an active chemical layer is formed, achieving high chemical activity without the need for high-temperature sintering. Trisodium methylglycine diacetate is used instead of tetrasodium glutamate diacetate, utilizing its smaller molecular weight to enhance penetration. The nitrogen-containing organic alcohol amine is triethanolamine.
[0016] Preferably, the dispersant is one of ammonium polyacrylate and polyaspartic acid; the regulator used to adjust the system to alkalinity is one of aminobutanol and triethanolamine. Ammonium polyacrylate has a CAS number of 9003-03-6 and a number-average molecular weight of 5000-8000. Polyaspartic acid replaces ammonium polyacrylate, enhancing biodegradability and corrosion inhibition; polyaspartic acid has a CAS number of 25608-40-6.
[0017] Preferably, the process of using the environmentally friendly water-based polishing slurry on the optical glass is as follows: the optical glass element is precision polished using the environmentally friendly water-based polishing slurry, CMP polishing is performed using a polyurethane foam pad with a hardness of Shore D of 55-60, and a 100-mesh diamond dressing disc is used simultaneously. Online dressing is performed every 3 discs for 2 minutes, the polishing pressure is 35-40 kPa, the polishing disc speed is 85-100 rpm, the polishing slurry flow rate is 120-150 ml / min and it is recycled, the polishing time is 12-15 minutes, after polishing, it is treated with 0.5% alkyl glycoside dilution at 40 kHz for 5 minutes, followed by ultrasonication, water washing, ultrasonication, and dehydration.
[0018] Preferably, the nano-cerium oxide emulsion is replaced with a mixture of nano-cerium oxide emulsion and colloidal silica. Deionized water is added to the reactor, along with tetrasodium glutamate diacetate and alkyl glycoside APG-0810 (carbon chain length C8-C10). A mixture of 150g nano-cerium oxide emulsion and 100g colloidal silica (SiO2) is pumped in at a rate of 10g / min. The temperature is raised to 45℃, and the mixture is stirred at 6000rpm under high shear for 2.0h. The colloidal silica is purchased from Fuso Chemical Industry Co., Ltd., Japan (PL-7), and its physicochemical information is as follows: appearance: milky white transparent liquid; D50: 80nm; SiO2 solid content: 40.5%; pH: 10.2 at 25℃; Na... + Content <100ppm, specific surface area 180m² 2 / g.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In existing technologies, fluorides or strong alkali modifiers are often introduced to enhance polishing activity. This not only makes the polishing solution highly corrosive and dangerous to operate, but also results in extremely high treatment costs for the discharged fluoride-containing wastewater. This invention introduces a bio-based chelating agent and a multifunctional organic amine buffer system, achieving zero-pollution emissions while replacing the corrosive effects of strong acids and alkalis through molecular-level chemical complexation. This significantly reduces the cost of industrial-scale environmental treatment and eliminates safety hazards during operation.
[0020] 2. Through a high-shear in-situ anchoring process, a transient high-energy field is used to precisely anchor the chelating agent and surfactant onto the surface of the nano-abrasive in a liquid phase environment, forming a stable molecularly modified layer. Compared to existing technologies that rely on solid-phase high-temperature sintering doping or simple one-pot mixing, this process avoids the risks of abnormal grain growth and soft agglomeration of the abrasive at high temperatures, ensuring the monodispersity of the slurry from the source. This significantly reduces the count of large particles and effectively solves the industry problem of micro-scratches easily generated in precision polishing.
[0021] 3. By utilizing the synergistic effect of long-chain polymeric dispersants ammonium polyacrylate / polyaspartic acid and modified abrasives, the absolute value of the system's Zeta potential is increased to above -50mV. The highly stable colloidal structure enhances the shear resistance and cyclic stability of the polishing slurry. Even under prolonged high-intensity polishing pressure, the abrasives maintain a narrow distribution, significantly improving the effective contact area and the efficiency of polishing pressure transmission, thus ensuring batch-to-batch consistency in processing quality.
[0022] 4. By using chelating agents to directionally soften the silicon-oxygen network on the K9 glass surface, combined with micromechanical exfoliation using nanoscale spherical abrasives, the material removal rate is increased to over 1500 nm / min through pre-softening followed by removal. Furthermore, the surface roughness is reduced to an atomic level below 0.3 nm, completely overcoming the bottleneck of limited sub-damage depth and the inability to further reduce Ra values caused by single mechanical cutting.
[0023] 5. The all-water-based green formulation used in this invention possesses excellent surface wettability and low residue characteristics. Through optimization of the ratio of nonionic surfactants to organic amines, the slurry can be rapidly desorbed by ultrasonic cleaning after polishing, with a residue count of <15 particles / cm³. 2 The yield is significantly lower than that of traditional silicone oil or polyether systems. This method not only has a simple preparation process and strong self-limitation, but also surpasses the existing technology level, possessing strong industrial application capability and wide applicability in optical processing. Attached Figure Description
[0024] Figure 1 This is a flowchart illustrating the preparation method of the environmentally friendly water-based grinding and polishing fluid for optical glass according to the present invention. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Please see Figure 1 This invention provides a method for preparing an environmentally friendly water-based polishing slurry for optical glass, the technical solution of which is as follows: Example
[0027] (1) Abrasive surface pretreatment and chelation induction: Add 720g of deionized water to a high-shear reactor, start stirring at 800rpm, then add 15g of tetrasodium glutamate diacetate chelating agent and 5g of alkyl glycoside surfactant sequentially, stirring for 20min to ensure complete molecular diffusion. Subsequently, pump in 250g of nano-cerium oxide emulsion at 10g / min, raise the temperature to 45℃, and maintain high-shear stirring at 4000rpm for 1.5h.
[0028] The preparation method of nano-cerium oxide emulsion is as follows: 1020g of cerium nitrate was dissolved in 1500ml of deionized water, and 5g of PEG-400 dispersant was added. Magnetic stirring was started at 500rpm until completely transparent. The role of PEG is to encapsulate the primary crystal nuclei and prevent the particles from becoming too large later. Under vigorous stirring at 1200rpm, 150ml of hydrogen peroxide (30% concentration) was slowly added to the cerium nitrate solution. At this time, the solution color changed from colorless to deep orange, forming a cerium peroxide complex. Subsequently, ammonia water was added dropwise at a rate of 15ml / min using a peristaltic pump, and the pH value of the system was strictly monitored. When the pH value reached 9.5, the dropwise addition was stopped, at which point a large amount of light yellow precipitate was produced. The obtained precipitate suspension was transferred to a high-pressure reactor and kept at a constant temperature of 160℃ for 12h. The hydrothermal environment promoted the transformation of amorphous cerium hydroxide to cubic fluorite CeO2 and caused the particles to spontaneously grow into spherical shapes. The hydrothermal product was separated by centrifugation. The supernatant was discarded, and the precipitate was washed repeatedly with deionized water 3-5 times until the conductivity of the centrifuged liquid was below 50 μS / cm. This step was to remove residual NH4+. 4+ and NO 3- Ions. The washed nanoparticles were redispersed in deionized water and circulated three times using a high-pressure homogenizer at a pressure of 800 bar. The moisture content was measured by a moisture analyzer. Finally, deionized water was added to precisely adjust the solid content to 40.3%, resulting in the finished nano-cerium oxide emulsion with an average particle size (D50) of 100 nm-120 nm.
[0029] By using tetrasodium diacetate of glutamate to in-situ molecularly coat the surface of CeO2 at a specific temperature to form an active chemical layer, high chemical activity can be obtained without high-temperature sintering.
[0030] (2) Steric hindrance stabilization of polymers: Add 10g of ammonium polyacrylate dispersant to the system, reduce the stirring speed to 1200rpm, and continue to disperse for 45min.
[0031] By utilizing the dual effects of charge repulsion and steric hindrance, the abrasive particle size distribution is locked, preventing soft agglomeration from causing scratches.
[0032] (3) System balance and precision purification: The pH of the system was stabilized to 10.2 using aminobutanol, and then circulated through an online ultrasonic homogenizing system at a flow rate of 60 L / h, a power of 800 W, and a frequency of 40 kHz for 30 min. Finally, it was filtered through a 0.2 μm polyethersulfone precision filter and packaged to obtain the finished product.
[0033] The environmentally friendly water-based polishing slurry prepared above was used to perform precision polishing tests on K9 optical glass components: constant temperature polishing at 22℃ was conducted using a 380-type single-sided precision polishing machine. CMP polishing was performed on a polyurethane foam pad with a Shore D hardness of 55-60, using a 100-mesh diamond dressing disc. Online dressing was performed every three discs for 2 minutes to maintain the microporous activity of the polyurethane polishing pad surface and prevent physical scratches caused by abrasive buildup. The polishing pressure was 35 kPa, the polishing disc speed was 85 rpm, the polishing slurry flow rate was 120 ml / min (circulated), and the polishing time was 15 minutes.
[0034] After polishing, the solution was treated with 0.5% alkyl glycoside dilution at 40kHz for 5 minutes, followed by high-frequency treatment with deionized water at 80kHz for 3 minutes, and finally dehydrated by slow lifting with isopropanol.
[0035] Example 2 (1) Abrasive surface pretreatment and chelation induction: Add 720g of deionized water to a high-shear reactor and start stirring at 800 rpm. Then add 15g of trisodium methylglycine diacetate and 5g of alkyl glycoside surfactant APG-0810 sequentially and stir for 20 minutes to dissolve them completely. Then pump in 250g of nano-cerium oxide emulsion at a rate of 10g / min and heat to 50℃. At this temperature, maintain high-shear stirring at 5000 rpm for 1.5 hours.
[0036] (2) Steric hindrance stabilization of polymers: Add 10g of ammonium polyacrylate dispersant to the above system, reduce the stirring speed to 1200rpm, and continue to disperse for 45min.
[0037] (3) System balance and precision filtration: The pH of the system was stabilized to 10.2 using aminobutanol. The polishing solution was then circulated through an ultrasonic circulation pipeline at a flow rate of 60 L / h for 30 min at a power of 40 kHz. Finally, it was filtered through a 0.2 μm polyethersulfone filter.
[0038] (4) Precision polishing test: A 380-type single-sided precision polishing machine was used, with parameters as described in Example 1. Due to the faster chelation kinetics of trisodium methylglycine diacetate, the polishing time was set to 12 minutes. The standard operating procedure (SOP) was the same as in Example 1.
[0039] Example 3 (1) Abrasive surface pretreatment and chelation induction: The parameters and proportions are exactly the same as in Example 1.
[0040] (2) Steric hindrance stabilization of polymers: Add 12g of polyaspartic acid to the system, adjust the stirring speed to 1800rpm, and continue to disperse for 60min.
[0041] (3) System balance and precision filtration: The pH of the system was adjusted to 10.0 using aminobutanol. The polishing solution was then passed through an ultrasonic circulation pipeline at a flow rate of 50 L / h, with the circulation time extended to 40 min and the power increased to 1000 W. Finally, it was precisely filtered through a 0.2 μm polyethersulfone filter.
[0042] (4) Precision polishing test: Because polyaspartic acid forms a tough molecular protective film, the polishing pressure is increased to 40 kPa, the polishing disc speed is maintained at 85 rpm, the flow rate is 120 ml / min, and the time is 15 min. The SOP operating procedure is the same as in Example 1.
[0043] Example 4 (1) Abrasive surface pretreatment and (2) Stabilization steps: The process and proportions are exactly the same as in Example 1.
[0044] (3) System balance and precision filtration: Triethanolamine was used as the pH adjuster. The pH of the system was stabilized at 9.8. The system was then subjected to ultrasonic circulation for 30 minutes and finely filtered.
[0045] (4) Precision polishing test: Since triethanolamine increases the viscosity of the slurry, the polishing fluid flow rate is increased to 150 ml / min to enhance the cooling effect. Polishing pressure is 35 kPa, rotation speed is 85 rpm, and time is 15 min. The standard operating procedure (SOP) is the same as in Example 1.
[0046] Example 5 (1) Abrasive surface pretreatment and chelation induction: Add 720g of deionized water to the reactor, add 15g of tetrasodium diacetate of glutamic acid and 5g of alkyl glycoside APG-0810, and pump in a mixture of 150g of nano cerium oxide emulsion and 100g of colloidal silica (SiO2) at a rate of 10g / min. Heat to 45℃ and maintain high shear stirring at 6000rpm for 2.0h.
[0047] (2) Steric hindrance stabilization of polymers: Add 10g of ammonium polyacrylate dispersant, adjust the speed to 1200rpm, and continue dispersing for 45min.
[0048] (3) System balance and precision filtration: The pH of the system was adjusted to 10.5 using aminobutanol, and the system was subjected to ultrasonic circulation for 30 minutes and then filtered.
[0049] (4) Precision polishing test: Utilizing the synergistic effect of rolling and sliding of the mixed abrasive, the polishing disc rotation speed was increased to 100 rpm, the pressure to 35 kPa, and the time to 15 min. The standard operating procedure (SOP) was the same as in Example 1.
[0050] The comparative design is based on Example 1, with some parameters adjusted as follows: Comparative Example 1 (1) Abrasive surface pretreatment: 735g of deionized water was added to the reactor. No tetrasodium glutamate diacetate or other chelating agents were added. Only 5g of alkyl glycoside surfactant was added. 250g of nano-cerium oxide emulsion was pumped in, the temperature was raised to 45℃, and high shear stirring was maintained at 4000rpm for 1.5h. (2) Stabilization and (3) Equilibrium filtration steps: all were carried out exactly as in Example 1.
[0051] Comparative Example 2 (1) Abrasive mixing: 720g of deionized water, 15g of tetrasodium diacetate of glutamic acid, 5g of alkyl glycoside and 250g of nano-cerium oxide emulsion were added to a mixing tank at the same time. A high-shear emulsifier was not used. A conventional paddle mixer was used. The mixture was mixed at 300rpm and 45℃ for 1.5h. (2) Stabilization and (3) Equilibrium filtration steps: All were carried out exactly as in Example 1.
[0052] Comparative Example 3 (1) Pretreatment and (2) Stabilization steps: all were carried out exactly as in Example 1. (3) System equilibration: instead of aminobutanol, potassium hydroxide (KOH) was used to adjust the pH of the system to 10.2±0.1. The ultrasonic circulation and filtration processes remained unchanged.
[0053] Comparative Example 4 (1) Pretreatment and (2) Stabilization steps: Refer to Example 1. (3) System equilibration: Refer to Example 1. However, in the batching stage, cerium oxide was replaced with alumina (Al2O3) abrasive of the same mass and particle size.
[0054] Test Example 1 All test results are the average of three measurements. The environmentally friendly water-based polishing slurries for optical glass prepared in the examples and comparative examples were subjected to material removal rate and surface roughness tests.
[0055] The removal rate test was conducted according to GB / T 30704-2014 and the general standard for semiconductor CMP, using a precision weighing method. The mass difference of the K9 glass element before and after polishing was measured using a 0.01 g analytical balance (sensitivity 0.1 mg), and the results were uniformly expressed in nm / min.
[0056] Surface roughness testing was performed according to GB / T 10610-2009, using a white light interferometer. Three points were randomly sampled on the polished K9 glass surface, with a sampling area of 20×20μm. 2 The test results are summarized in Table 1.
[0057] Table 1. Results of material removal rate test and surface roughness test Example 1 1420.55±1.12% 0.284±1.85% Example 2 1485.32±1.45% 0.291±2.1% Example 3 1362.40±0.85% 0.265±1.42% Example 4 1290.18±2.34% 0.312±3.25% Example 5 1530.76±3.1% 0.345±4.8% Comparative Example 1 915.20±5.85% 0.620±8.42% Comparative Example 2 1150.45±12.4% 1.152±15.6% Comparative Example 3 1620.10±4.25% 0.885±9.33% Comparative Example 4 1850.33±7.6% 2.450±8.25% The test results show that Examples 1-5 all achieved a balance between high-efficiency removal with an MRR > 1200 nm / min and an ultra-smooth surface Ra < 0.4 nm. Example 5, due to the introduction of Ce / Si hybrid abrasive, utilized the mechanical grinding effect of silica combined with the chemical activity of cerium oxide, achieving the highest MRR. Example 2, due to the stronger small-molecule penetration and chelating power of trisodium methylglycine diacetate, also showed a significantly better MRR than Example 1. Example 3 performed best, with a Ra as low as 0.265 nm, attributed to the dense, flexible molecular film formed by polyaspartic acid on the abrasive surface. Even with polishing pressure increased to 40 kPa, this film still provided excellent buffering lubrication, greatly reducing the possibility of micro-stress concentration.
[0058] Comparative Example 1 showed a significant drop in material removal rate to below 1000 nm / min, demonstrating that the chemical weakening of Si-O-Si bonds on the K9 glass surface by tetrasodium glutamate diacetate chelating agents is a prerequisite for efficient processing. Without chemical energy, pure mechanical grinding is inefficient. Comparative Example 2, while showing a acceptable MRR, exhibited a Ra value exceeding 1 nm, indicating the absence of high-shear process-induced molecular anchoring. The abrasive was in a soft agglomerate state, and the microscopic particle size inhomogeneity directly led to numerous fine scratches on the glass surface. Comparative Example 3, while showing the highest MRR, was primarily due to the extremely strong corrosiveness of the inorganic alkali to the glass. However, its Ra value was unacceptable, and the strong alkali caused non-selective isotropic etching, resulting in microscopic pits on the glass surface, highlighting the organic buffering value of aminobutanol. Comparative Example 4 exhibited the highest removal rate but the worst surface quality. The high hardness of alumina, in the absence of chemical synergy, acted entirely on the K9 glass through forceful cutting. Although the peeling speed was fast, the resulting sub-damage layer and scratch depth were extremely high, failing to meet precision optical requirements.
[0059] The quality of polishing slurry depends not only on processing efficiency (MRR), but also on the physicochemical stability of the system and the control of sub-damage to optical components. Test Example 2 focuses on the colloidal properties of the slurry and its post-processing performance. The specific test methods for Test Example 2 are as follows: To ensure that the data meets the stringent requirements of optical glass processing, all tests were conducted in a constant temperature environment of 22±1℃ for 24 hours. The large particle counting LPC uses single-particle optical sensing technology. 10ml of the original slurry was taken, diluted online with deionized water at a volume ratio of 1:100, and then passed through the sensor.
[0060] The Zeta potential value is based on GB / T 32668-2016. The larger the absolute value, the stronger the electrostatic repulsion between particles and the more stable the system.
[0061] The surface residue count after cleaning was performed according to the semiconductor cleanliness evaluation standard. The polished and cleaned K9 glass was placed under a high-power dark-field microscope, and the residue per unit area (cm²) was counted. 2 Residual particles and organic matter sites with an inner diameter > 0.1 μm.
[0062] The test method for static etching rate (SER) is as follows: K9 glass is immersed in a constant temperature polishing solution at 45℃ and left to stand for 6 hours. The thickness loss is calculated by weighing with a precision analytical balance. The final test results are shown in Table 2.
[0063] Table 2 Summary of Physicochemical Properties and Stability Test Results Example 1 1.85±2.12% -45.6±1.20% 12.3±3.20% 0.45±0.13% Example 2 2.10±2.45% -42.1±1.55% 15.6±3.45% 0.62±0.14% Example 3 1.25±1.50% -51.3±0.95% 8.4±2.85% 0.38±0.10% Example 4 2.55±3.80% -38.4±2.60% 10.2±4.10% 0.55±0.15% Example 5 3.42±4.95% -35.2±3.15% 18.7±5.50% 0.48±0.17% Comparative Example 1 5.20±6.50% -32.5±4.20% 35.8±8.10% 0.12±0.27% Comparative Example 2 25.40±18.2% -22.1±9.50% 142.5±15.4% 0.44±0.36% Comparative Example 3 4.85±5.20% -28.6±5.10% 65.2±9.25% 3.15±0.71% Comparative Example 4 8.65±7.40% -15.4±8.80% 88.3±11.2% 0.05±0.76% The results of Examples 1-5 above demonstrate excellent colloidal stability and environmentally friendly, easy-to-wash properties. Example 3, due to the strong steric hindrance effect provided by the long polymer chains, exhibits the highest absolute value of the Zeta potential and the lowest LPC count, proving that it achieves a good monodisperse state under energy field synergy. Example 4 utilizes the lubricating properties of triethanolamine, demonstrating excellent residue control. Overall, the static etching rate of the example groups is controlled below 1.0 nm / min, ensuring a controlled polishing process and preventing surface roughening caused by over-etching.
[0064] Comparative Example 1 exhibited an extremely low static etching rate, indirectly confirming the lack of chemical softening capability. However, due to the lack of chemical polar groups modifying the abrasive, the LPC (Liquidity Perceptual Process) increased significantly compared to the Example 1, leading to an increase in residual particles after cleaning. Comparative Example 2 showed a high large particle count, primarily due to the lack of a high shear energy field. The abrasive surface failed to form an effective molecular anchoring layer, and particles aggregated into soft agglomerates under van der Waals forces. These agglomerates not only easily leave residues on the surface but were also the root cause of the excessive Ra value in Example 1. Comparative Example 3 showed an extremely high static etching rate. Strong alkaline inorganic ions directly damaged the silicon-oxygen network of the glass, representing a typical case of chemical over-etching. Although the removal rate was high, the high concentration of inorganic salt ions reduced the double layer thickness and the absolute value of the Zeta potential, causing the slurry to easily agglomerate and be extremely difficult to rinse clean. Comparative Example 4 has the lowest Zeta potential and is in the colloidal unstable region. The alumina particles have a high isoelectric point in the water-based system, which is poorly matched with the existing anionic dispersants, making the system very easy to settle. Although its chemical corrosion is almost zero, the residues generated by physical accumulation and the extremely high mechanical stress are the core reasons for its failure.
[0065] Compared to the polishing slurries prepared using conventional low-energy stirring processes, strong alkali conditioning, or single hard physical grinding in the comparative example, the polishing slurries have poor polishing rates, surface roughness, and colloidal stability due to unreliable adsorption on the abrasive surface, lack of chemical softening, or severe non-selective etching.
[0066] This invention presents an environmentally friendly water-based polishing slurry prepared through a high-shear in-situ anchoring process and a bio-based multi-toothed chelation system. This slurry not only exhibits a high polishing rate but also extremely low surface roughness. Furthermore, it demonstrates a high absolute value of the zeta potential and a very low count of large LPC particles, indicating that the polishing slurry prepared in this invention achieves precise modification of the abrasive at the molecular level, exhibiting excellent monodispersity and chemimechanical synergy.
[0067] This invention features a scientifically designed and highly self-limiting process, achieving a balance between environmental friendliness and performance in its component ratios. The resulting polishing slurry not only surpasses existing technologies in processing efficiency but also exhibits low residue counts, controlled static etching, and superior surface integrity protection. This approach eliminates the need for traditional fluoride and strong alkali systems, possessing excellent biodegradability and process stability. It is widely applicable to semiconductor-grade polishing of precision optical components such as K9 glass, demonstrating significant industrial application value and practicality.
[0068] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly water-based polishing slurry for optical glass, characterized in that, The preparation method is as follows: Deionized water, chelating agent and alkyl glycoside surfactant are added to a high-shear reactor, dissolved and then pumped into nano-cerium oxide emulsion. The mixture is stirred and heated to obtain an active emulsion. The chelating agent is one of a multidentate amino acid chelating agent and a nitrogen-containing organic alcohol amine. A dispersant was added to the active emulsion, the rotation speed was reduced and the mixture was dispersed, the system was adjusted to alkalinity, and then ultrasonicated and filtered to obtain the environmentally friendly water-based grinding and polishing slurry for optical glass. The nano-cerium oxide emulsion is obtained by treating cerium nitrate with polyethylene glycol, complexing with hydrogen peroxide, precipitating with ammonia, hydrothermal crystallization, washing, homogenizing, and adjusting the solid content.
2. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The multidentate amino acid chelating agent is selected from one of tetrasodium glutamate diacetate and trisodium methylglycine diacetate; the nitrogen-containing organic alcohol amine is triethanolamine; the heating temperature is 45-50℃; the stirring speed is 4000-5000 rpm; and the dispersion speed is 1200 rpm.
3. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The dispersant is one of ammonium polyacrylate and polyaspartic acid; the regulator used to adjust the system to alkalinity is one of aminobutanol and triethanolamine; the pH of the alkaline environment is 9.8-10.
5.
4. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The preparation method of the nano-cerium oxide emulsion is as follows: dissolve the cerium nitrate in the deionized water, add the polyethylene glycol dispersant, and stir magnetically until transparent to obtain a cerium nitrate solution; add hydrogen peroxide to the cerium nitrate solution for complexation; add ammonia water dropwise to produce a precipitate, perform a hydrothermal reaction at a constant temperature, and after solid-liquid separation, wash, homogenize, and adjust the solid content to obtain the nano-cerium oxide emulsion.
5. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The ultrasound circulation rate is 50-60 L / h, the power is 800-1000 W, and the circulation time is 30-40 min.
6. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The process of using the environmentally friendly water-based polishing slurry on the optical glass is as follows: The optical glass element is precision polished using the environmentally friendly water-based polishing slurry. CMP polishing is performed using a polyurethane foam pad with a hardness of Shore D of 55-60. At the same time, a 100-mesh diamond dressing disc is used. Online dressing is performed every 3 discs for 2 minutes. The polishing pressure is 35-40 kPa, the polishing disc speed is 85-100 rpm, and the polishing slurry flow rate is 120-150 ml / min for recycling. The polishing time is 12-15 minutes. After polishing, the glass is cleaned for 5 minutes under 40 kHz ultrasonic conditions using a 0.5% alkyl glycoside dilution solution. After ultrasonication, the glass is washed with water and then dehydrated.
7. The method for preparing an environmentally friendly water-based polishing slurry for optical glass according to claim 1, characterized in that, The nano-cerium oxide emulsion was replaced with a mixture of the nano-cerium oxide emulsion and colloidal silica.
Citation Information
Patent Citations
Preparation method of nano CeO2 polishing powder
CN105733445A
Nanometer cerium oxide polishing solution and preparation method thereof
CN110041831A